The INTERNALIZING THE VALUES OF CULTURAL PLURALISM TO STUDENTS THROUGH ANNUAL CEREMONIES AT THE WALI SONGO NGABAR ISLAMIC BOARDING SCHOOL: The Values of Cultural Pluralism - Zahara, Aulia Jihan (Institut Agama Islam Riyadhlotul Mujahidin Ngabar (IAIRM) Ponorogo, 2025)
This study aims to examine how the annual ceremony at the Wali Songo Ngabar Islamic Boarding School can be an effective means of internalizing the values of cultural pluralism among students. Using a qualitative approach through participant observation, in-depth interviews, and document analysis, this study found that these activities not only strengthen solidarity among students from various cultural backgrounds but also promote understanding of tolerance and appreciation for diversity. The results show a 75% increase in awareness of pluralism based on pre- and post-activity surveys, with positive implications for the formation of a more inclusive character among students. This research contributes to the development of character education through annual assemblies at modern Islamic boarding schools, with regular annual activities serving as a tool for internalizing social values.